Finite Element Models of Disk Tools with Attachment Points on Triangular Prisms - Khoreshok A. A. Aleksey Alekseevich; Mametyev L. E.; Borisov A. Y.; Vorobyev A. V. Aleksey Vasilievich (Designing and Modelling of Machines and Mechanisms, 2015)
Title screen